Pengaruh Kompetensi Pedagogi Guru dan Fasilitas Belajar Terhadap Minat Belajar Siswa Kelas XI SMK Penda 2 Karanganyar - Lintang Asmbari; Hery Sawiji; Patni Ninghardjanti (Politeknik Kampar, 2025)
This study aims to: 1) Knowing the effect of Teacher Pedagogical Competence on Learning Interest of Grade XI Students in the Department of Automotive Light Vehicle Engineering, Industrial Mechanical Engineering, and Fashion Management of SMK Penda 2 Karanganyar. 2) Knowing the effect of Learning Facilities on Learning Interest of grade XI students in the Department of Automotive Light Vehicle Engineering, Industrial Mechanical Engineering, and Clothing Layout of SMK Penda 2 Karanganyar, and 3) Knowing the effect of Teacher Pedagogical Competence and Learning Facilities together (simultaneously) on Learning Interest of grade XI students in the Department of Automotive Light Vehicle Engineering, Industrial Mechanical Engineering, and Clothing Layout of SMK Penda 2 Karanganyar. This research is a correlational quantitative research. The population in this study were grade XI students in the TKRO, TMI, and TB Departments of SMK Penda 2. The sampling technique was carried out by simple random sampling with a total sample of 211 students. Data collection was done by observation, questionnaire, and interview. The validity and reliability test technique used in this study used the help of SPSS 25. The data analysis technique used multiple linear regression analysis with the IBM SPSS 25 program. The results showed that: 1) There is a positive and significant effect of teacher pedagogical competence on learning interest. This has been proven by tcount> ttable (1.982> 1.971). From these data it can be said that (H0) is rejected and (H1) is accepted. 2) There is a positive and significant effect of learning facilities on interest in learning. This is evidenced by thitung>ttabel (2.275>1.971). From these data it can be said that (H0) is rejected and (H2) is accepted. 3) There is a positive and significant effect of teacher pedagogical competence and learning facilities together on interest in learning, this is evidenced by Fcount>Ftabel (3.886>2.110) with a significance level of 0.022 <0.05. From these data it can be said that (H0) is rejected and (H3) is accepted.